Somatic embryogenesis for plant production of Abies lasiocarpa - Kvaalen, H.; Daehlen, O.G.; Rognstad, A.T.; Gronstad, B.; Egertsdotter, U.
Seeds of Abies lasiocarpa (Hook.)Nutt. (subalpine fir)were dissected, and the different parts were analyzed for elemental composition. The data were used to design a novel growth medium for initiation of somatic embryogenesis. Embryogenic cultures were initiated from immature zygotic embryos from six open-pollinated families of A. lasiocarpa on three different media. The frequency of initiation was the highest in early to mid-July when the zygotic embryo explants were ca. 0.8 mm long. Thereafter the response declined rapidly. The culture media did not significantly affect the initiation frequencies, but the subsequent growth and culture survival was dependent on the culture medium. On the Schenk Hildebrandt medium, many cultures ceased to grow and died. Several of the decaying cultures were rescued after transfer to one of the new media. Proliferating cultures could be stimulated to produce mature embryos. Of 2510 mature somatic embryos, 212 (8.4